METHODOLOGY FOR QUANTITATIVE ASSESSMENT OF THE MARSH BIOTOPS DISTRUCTION OF THE RIVERS IN THE NORTH BLACK SEA COAST AREA - Мазур, І.О. (World of Medicine and Biology, 2016)
It has been developed and successfully tested the methodology for unified assessment of the destruction level and state of steppe rivers marsh biotopes which is based on the quantitative criteria – the marshiness coefficient. It can be applied to evaluate retrospective, present and prognostic state of marshes as highly dynamic and ecologically vulnerable environmental complexes. Testing of this method was made on the steppe rivers of the Tylihul-Buh interfluve in the 2012-2016. The results of recent seasonal and long-term as well as retrospective assessment of marsh destruction made it possible to establish a number of geographical and ecological-hydrological patterns in marsh ecosystems functioning of the unstable flow rate of the river valleys. At the same time, marshiness coefficients are closely adjusted to the salinity parameters of local wetland areas and types of prevailing phytocommunity.